Depression in people, that live with HIV in Lima - Fasce Cayo, Ninoshka (2002)
The study investigates the depression in a group 55 adults (14 women and 41 men) who live with VJH, between 18 and 58 years, oflow and medium low socioeconomic leve! which attend public health centers, NGO and mutual support groups (MSG) of Lima. The Beck Depression Inventory was used to study the level of depression, as well as the five factors found in this population.The descriptive results were correlated with the following demographic variables: age,sex, time of diagnosis, the presence or absence of symptoms associated to VIH, the participationor not in a MSG, sexual orientation and sex. Results indicated that depression varies depending on whether the person belongs or not to a MSG, sex and sexual orientation.